Measuring continuity of ambulatory cardiovascular care: a cross-sectional study on the applicability of the Nijmegen Continuity Questionnaire in Germany - Hennrich, Patrick; Arnold, Christine; Koetsenruijter, Jan; Wensing, Michel (BMC health services research, 2022)
Chronic cardiovascular diseases demand continuous care from general practitioners and medical specialists. Especially in fragmented healthcare systems, such as in Germany, a large body of research is devoted to the improvement of care continuity. Meanwhile, measuring continuity of care itself has been a challenge due to the absence of validated instruments. In 2011, the Dutch Nijmegen Continuity Questionnaire (NCQ) was developed and validated to measure continuity of care across care settings from the patients’ perspectives in the Netherlands. Its applicability in other countries and health systems, however, has rarely been tested. We therefore aimed at assessing the applicability of the Nijmegen Continuity Questionnaire to the German health care context.
Gesehen am 19.10.2022